Global, regional, and national burden of esophageal cancer using the 2019 global burden of disease study - Liangchao Sun; Kaikai Zhao; Xiaoli Liu; Xue Meng (Scientific Reports)
Abstract Esophageal cancer, with its aggressive nature and high mortality, poses diverse epidemiological challenges worldwide. Over the past three decades, esophageal cancer has exhibited a substantial global burden, marked by a significant increase in absolute numbers, contrasting with a decline in age-standardized metrics. Prevalence nearly doubled, reaching 0.961 million in 2019, while the age-standardized rate (ASR) decreased to 11.6 per 100,000 cases. New incidence cases surged by 67.07%, yet the age-standardized incidence rate reduced to 6.5 per 100,000 cases. Deaths increased to 0.498 million, with a decline in age-standardized mortality to 6.1 per 100,000 cases. Disability-Adjusted Life Years (DALYs) rose to 11.67 million, but the ASR decreased to 139.8 per 100,000 cases. Gender-specific analysis revealed consistently higher rates in males, with increasing gaps over time. Correlations with SDI indicated a negative association, and frontier analysis underscored the impact of socio-economic progress on disease control. Projections suggest a continued rise in prevalence, incidence, deaths, and DALYs, with gender-specific variations. The research underscores the importance of continued efforts in public health and medical research to adapt to and manage the changing landscape of esophageal cancer globally.